Extension strategy and institutional mechanism for biodiversity conservation - D. Sen, (Journal of Agricultural Extension Management, 2025)
Nature provides us with food and all the raw materials we make use of in both traditional as well as modern societies. Conservation of natural resources is, therefore, by extension, the conservation of human life . The Brundtland Commission 's report "Our Common Future" highlighted the need for mobilizing the forces of change for achieving better balance between humankind and nature, ensuring thereby a safer and better world for all (WCED, 1987). One of the ways for maintaining such balance was suggested at the United Nations Conference on Environment and Development in 1992 ( otherwise known as Rio Summit and "Earth Summit"), to hold an intergovernmental convention on ways and mean s for protecting species and habitats. Environmental groups and the press nicknamed it as the "Bio Diversity Convention". "Bio Diversity" is in real term a contraction of "Biological Diversity". At the most general level, it refers to the variety to be found among the living organisms throughout the earth. This variety enriches the Universe and our own culture by virtue of its existence and the desire that it should be maintained in the best way possible. Accompanying this feeling, is the fear that species are getting extinct at a rate unprecedented in recent history, and therefore, the variety of organisms is being eroded. These views, and the fear are shared by most of the environmentalists. Along with the variety of species, biodiversity should also take into account the genetic diversity reflected in the entire global gene pool. In that case, it is not only species we must preserve, but the genetic variation within each population of every species also has to be taken into account. Alternatively, we might seek to protect eco systems by identifying and safeguarding each small area of habitat (Allaby, 1996)